Don Juan on the Internet: on the quality of digital literature - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2018)
The aim of the present article is to analyse the phenomenon of graphomania on the Internet, with Marina Maslova’s 2004 novel Don Juan as an example. The choice of the text was dictated by the interest in the presence of the eternal image of Don Juan in the Internet space and in the transformations it undergoes there. Taking Maslova’s text as an example, the author of the paper identifies and names essential features of digital literature, among others: derivativeness (non-originality) of literary images, a tense and attractive story, a twisted plot, stereotypical devices, a limited stock of literary images and motifs, the poetics of everyday life, permanent dynamism, polyauthorism, violation of the distance between the author and the text. The analysis of Maslova’s novel makes it possible to identify also the mechanisms of transformations applied to the image of Don Juan in the Internet space. In that connection, it is noted that the discussed writer only takes interest in certain selected situations and motifs from Don Juan’s story, adapts them to the genre of the romance novel, displays a free approach to the literary tradition and deprives the eponymous figure of autonomy in terms of plot.